Pharmacoeconomic analysis of Anti-inhibitor coagulant complex (AICC) in the treatment of inhibitor hemophilia - R. I. Yagudina; I. Yu. Zinchuk (Фармакоэкономика)
based on the clinical study FENOC, indicated that there is no significant difference in efficacy AICC and Eptacog alfa therapy in patients susceptible to this treatment. An analysis of the direct and indirect costs shows that the costs of the annual course of treatment of 142 patients in Russia are 66 mil EUR, 60,7 mil EUR and 53,1 mil EUR for treatments Eptacog alfa monotherapy, «Eptacog alfa + AICC» and «AICC + Eptacog alfa» schemes respectively. It is determined that the regimen «AICC + Eptacog alfa», will reduce reduces costs relative to the current treatment regimen for 12,9 mil EUR (19,54%) or provide additionally treat of 34 patients of this disease.